The Effect of the Pattern of Lateral Preference of Eye and Hand on Learning Basketball Free Throw Skill - Tayebe Taherpouri; Parvaneh Shafineya; Mahdi Zarghami (University of Tehran, 2016)
Various researches know lateral preference of eye and hand pattern as one of the important factors of performing sports skills. This study aimed at investigating the effect of lateral preference of eye and hand pattern on learning basketball free throw skill. From 3000 female students of Shahid Chamran University of Ahvaz, 60 subjects (age range 19-22 yr) were selected purposively as the sample using a researcher-made questionnaire of individual information and sporting background, Edinburgh Handedness Inventory (Oldfield, 1971) and hole card (Durand and Gold, 1910) and were assigned to two control and experimental groups (each group: 15 unilateral subjects and 15 crossed-lateral subjects). Firstly, pretest of basketball free throw was conducted. Then, practice protocol was performed for 8 weeks (24 sessions, 3 sessions a week). During this period, 6 posttests were administered to determine learning stages and one week after the last posttest, the retention test was conducted. The results showed a significant difference between unilateral and crossed-lateral (experimental group) subjects in the cognitive (sig=0.000) and associative (sig=0.000) stages of the acquisition of basketball free throw and the unilateral subjects had a better performance. Whereas there was no significant difference between unilateral and crossed-lateral subjects in the autonomous (sig=0.105) and retention (sig=0.086) stages. Finally, the results showed a difference in performance between experimental and control groups in favor of experimental group. According to these results, it seems that long practice and autonomous skill in unilateral and crossed-lateral subjects matched their performance and eliminated their differences. Therefore, coaches are recommended to identify talented subjects after a lot of practice in order to not generalize the result of performance to learning.